Deer habitat in western Costa Rica: Impacts of changing technology and land use - Lynn R., Irby (1996)
White-tailed deer (Odocoileus virginianus) numbers on the Pacific Coast of Costa Rica probably peaked in the nineteenth century as native dry tropical forest was converted to shrubland and secondary forest. Overhunting and conversion of forest to crops and ex- otic grasses led to declines in deer through most of the 1 900s. Current population levels are low, but restoration efforts may succeed partially as a result of incursions of modern technology and land-use changes. Power lines were built along several roads in the southern end of the Nicoya Peninsula of western Costa Rica in the 1 970s and 1 980s. Ac- cess to electricity and economic and social changes at the national level led to land-use changes in the Nicoya Peninsula including consolidation of land holdings, diversification of agricultural operations, and reductions in the number of subsistence farms. Compar- isons of topographic maps based on 1945 aerial photos with ground observations in 1989-1 990 indicated that: (1) rural houses and roads in the study area did not increase between 1945 and 1990 despite population increases in Costa Rica; (2) closed-canopy tree cover may have increased as much as 4-fold; and (3) rural housing distribution changed substantially, and the change was related to power-line distribution. Availabil- ity of electric power likely influenced changes in distribution of the human population and attitudes towards wildlife; these changes resulted in an increase in habitat available to wildlife and increased tolerance for several species of wild vertebrates, neither of which would have been predicted by the environmental impact models proposed by op- ponents of technology